Rickettsia sibirica mongolitimonae infection, Sri Lanka: Rickettsia sibirica mongolitimonae infection - Cordier, Charlotte; Tattevin, Pierre; Leyer, Caroline; Cailleaux, Marine; Raoult, Didier; Angelakis, Emmanouil (The Journal of Infection in Developing Countries, 2017)
Introduction. Rickettsia sibirica mongolitimonae was recently reported as a common rickettsiosis in France. Current serological evidence suggests the presence of scrub typhus and spotted fever group rickettsiosis in Sri Lanka. We detected a human case of R. sibirica mongolitimonae in Sri Lanka. Methodology. A skin biopsy of the eschar was tested for the presence of Rickettsia spp. using qPCR assay targeting a 109-bp fragment of a hypothetical protein and by PCR amplification and sequencing targeting the ompA gene. Results. A 30-year-old woman who had just returned from travel to a jungle in Sri Lanka was evaluated as an outpatient for fever. Examination revealed an enlarged axillary lymph node, a maculopapular rash and an eschar at her left flank and a skin biopsy of the eschar was performed. The skin biopsy was positive for the presence of Rickettsia spp. by qPCR and PCR amplification and sequencing targeting the ompA gene revealed R. sibirica mongolitimonae. Immunofluorescence assay on an acute serum sample for spotted fever group rickettsial antigens (Rickettsia conorii conorii, R. sibirica mongolitimonae, Rickettsia felis) and typhus group rickettsiae (Rickettsia typhi) was negative. The patient was treated by oral doxycycline (200 mg/day) for one week. Conclusions. R. sibirica mongolitimonae should be considered in the differential diagnosis of patients with suspected rickettsiosis in, or returning from, Sri Lanka.